Chaotic Synchronization of Modified Discrete-Time Tinkerbell Systems - Ke Ding; Xing Xu (Discrete Dynamics in Nature and Society)
This paper studies chaotic synchronization of modified discrete-time Tinkerbell systems. By constructing the Lyapunov function and using the linear feedback control, some synchronization criteria for modified discrete-time Tinkerbell systems are derived. The conservativeness of those synchronization criteria is compared. The effectiveness of derived results is demonstrated by six examples.